ChemInform Abstract: Efficient Synthesis of Quinolines via a Knoevenagel/Staudinger/Aza‐Wittig Sequence. Issue 17 (April 2016) - Qu, Feng; He, Ping; Hu, Ruo‐Fei; Cheng, Xiao‐Hong; Wang, Song; Wu, Jing
Abstract: A great variety of quinoline derivatives is simply and efficiently synthesized from 2‐azidobenzaldehyde (I) and various carbonyl compounds in good yields through a Knoevenagel condensation followed by an intramolecular Staudinger/aza‐Wittig reaction.